Irrigation and plant diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Most of the plant diseases caused by fungi, bacteria or viruses, as well as those introduced by fauna (for instance worms) depend on climatic conditions for their propagation. It is difficult to make generalisations on this, since each cultivated...